Integrating Global Citizenship Competencies into General Education: A Basis for an Enhanced Curriculum Guide in Philippine Higher Education - Alvero, John Cliford (Journal of Interdisciplinary Perspectives, 2025)
Preparing students to become responsible global citizens is essential in today’s interconnected world. This study explored how well Global Citizenship Competencies (GCCs) are integrated into General Education Courses (GECs) in higher education. Specifically, it assessed students' achievement of GEC learning outcomes, their awareness of Global Citizenship Education (GCED) concepts, the extent of GCC integration, and the acceptability of a proposed curriculum guide. Using a descriptive-developmental design, data were gathered from 310 students and 27 GEC teachers through surveys and interviews. Results showed that students had only a low level of achievement in GEC learning outcomes and limited awareness of GCED concepts. Teachers rated GCC integration as moderate, while students rated it as low, showing a clear gap in instruction and understanding. However, deans, curriculum experts, and faculty members rated the enhanced curriculum guide highly acceptable. These findings highlight the need to improve curriculum content and teaching strategies to integrate global citizenship education better. The study recommends adopting the enhanced curriculum guide to help higher education institutions prepare students with the values, skills, and understanding needed to face global challenges.